SASTRA MUSLIM DAN ARAB DI AMERIKA - Herman Felani (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2024)
Islamophobia has become a serious problem in many countries around the world. In America, especially after the September 11, 2001 attacks, Muslim and Arab minority groups have become targets of Islamophobic and Xenophobic hatred and discrimination. This study aims to provide an overview of how the voices of Arab and Muslim minorities in literary works written by Muslim writers or of Arab descendants in America. This research is qualitative research using a literature review approach. This research argues that American Muslim and American Arab existed as one of the minority literatures in the diverse American subcultures. The classification of the American Muslim and Arab literature is based on the political movement, philosophy, and racial and cultural affiliation. The study found that American writers who are Muslim and Arab descent through literature attempt to represent their identity as part of America the same as other citizens even though they face discrimination and become targets of xenophobia in their daily lives.